2019
DOI: 10.3389/fendo.2019.00044
|View full text |Cite
|
Sign up to set email alerts
|

Novel Splicing of Immune System Thyroid Stimulating Hormone β-Subunit—Genetic Regulation and Biological Importance

Abstract: Thyroid stimulating hormone (TSH), a glycoprotein hormone produced by the anterior pituitary, controls the production of thyroxine (T4) and triiodothyronine (T3) in the thyroid. TSH is also known to be produced by the cells of the immune system; however, the physiological importance of that to the organism is unclear. We identified an alternatively-spliced form of TSHβ that is present in both humans and mice. The TSHβ splice variant (TSHβv), although produced at low levels by the pituitary, is the primary form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 76 publications
0
8
0
Order By: Relevance
“…Finally, TSH level is intensively related to iodine status, and iodine deficiency can result in increased TSH level (17,73). Some studies found that TSH have an important role in regulating both the function of the immune system and immune response (74,75,76,77,78,79,80,81). Therefore, the increased TSH level among hypothyroidism individuals caused by iodine deficiency may induce aberrant immune response and further promote the development of TAI.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, TSH level is intensively related to iodine status, and iodine deficiency can result in increased TSH level (17,73). Some studies found that TSH have an important role in regulating both the function of the immune system and immune response (74,75,76,77,78,79,80,81). Therefore, the increased TSH level among hypothyroidism individuals caused by iodine deficiency may induce aberrant immune response and further promote the development of TAI.…”
Section: Discussionmentioning
confidence: 99%
“…AS is a key regulatory factor in the diversity of protein translation and gene phenotype, which is not only involved in normal physiological process but also plays an important role in the occurrence and development of human diseases, including PTC. For example, the alternatively spliced variant of thyroid stimulating hormoneβ (TSHβ), TSHβv (exon 2 deleted, exon 3 retained) has been associated with autoimmune thyroiditis in humans, which is also a high-risk factor for thyroid carcinoma ( 30 ). Circadian clock-independent AS events that play an important role in the homeostasis of the endocrine system, such as alternatively spliced Clock and Bmal1 , are regulated by thyroid hormone receptor-associated protein 3 (THRAP3) and are closely associated with endocrine diseases including PTC ( 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…A decade ago was discovered a splice variant of the tshb gene in mice ( 197 ) and human ( 198 ). This variant is made of the 3’ end of the last intron of tshb that now encodes a nine-amino acid-long stretch that presents features in agreement with a signal peptide ( 199 ) and the last exon of tsb , generating an N-terminally truncated β subunit. This protein lacks amino acids encoded by the first encoding exon and notably one each of the three paired-cysteine residues involved in the cystine-knot plus one that normally buckles the carboxyl end « seatbelt » of the β subunit around the α subunit ( Figure 1 ).…”
Section: Unconventional Actions Of Gphs or Their Subunitsmentioning
confidence: 99%
“…Bone marrow cells were shown to express very little amount of the GPHα subunit ( 198 ) if any ( 202 ). Even if some role has been attributed to the truncated variant from macrophages in osteoprotection ( 202 ), in immune response with the variant expressed in leucocytes homing to the thyroid after systemic bacterial infection ( 199 , 203 ) and in the pathology of Hashimoto’s Thyroiditis patients ( 205 ), the way this variant may achieve these functions remains to be deciphered. It has to be reminded that the TSHβ variant consists of part of the last intron directly attached to the last exon of the tshb .…”
Section: Unconventional Actions Of Gphs or Their Subunitsmentioning
confidence: 99%